Analisis Strategi Digital Marketing Usaha Kuliner Dengan Pendekatan Swot: Studi Kasus Bunda Nasrullah Food - Nasrullah Adiyatma Hakim; Dedy Husrizal Syah (Jurnal Nasional Teknologi Komputer, 2025)
This research aims to analyze the digital marketing strategy implemented by Bunda Nasrullah Food, a local culinary business that offers home-cooked meals with the added value of halal certification. The SWOT approach is used to identify the strengths, weaknesses, opportunities, and threats in the digital marketing strategy carried out through social media, e-commerce, and other digital platforms. The analysis reveals that the main strengths of Bunda Nasrullah Food are its authentic taste, affordable pricing, and certified halal assurance. Meanwhile, its weaknesses include inconsistent digital content and suboptimal branding management. There are significant opportunities through the growing trend of halal food consumption and MSME digitalization, yet threats arise from intense competition in the online culinary market. This study recommends strengthening the halal brand identity, optimizing social media engagement, and collaborating with local influencers as sustainable digital marketing strategies.